A first principles study of spinel ZnFe2O4 for electrode materials in lithium-ion batteries. Issue 38 (22nd September 2017) - Guo, Haoyue; Zhang, Yiman; Marschilok, Amy C.; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Liu, Ping
Abstract : The interplay among Li, O 2−, Fe 3+ and Zn 2+ enables the high performance of ZnFe2 O4 as Lithium ion battery materials. Abstract : Zinc ferrite (ZnFe2 O4 ) is a prospective lithium ion battery (LIB) material, owing to its large theoretical capacity (1000 mA h g −1 ). Here, we report a density functional study of the discharge process at an early stage from ZnFe2 O4 up to Li x ZnFe2 O4 ( x = 2), aiming to provide a fundamental understanding of the mechanism. According to our calculations, with x increasing up to 1 the intercalation of Li + ions prefers octahedral 16c sites, which is accompanied by Zn 2+ ion displacement from tetrahedral 8a sites to 16c sites starting at x = 0.25 and a gain in stability, while the stability decreases for 1 < x ≤ 2 due to the occupation of Li + ions at the less active tetrahedral 8a/48f/8b sites. The open-circuit voltages estimated based on the structures of stable intermediates identified by DFT calculations are in good agreement with the experimental values. Our results highlight the importance of the interplay among Li, O 2−, Fe 3+ and Zn 2+ in enabling their high performance as LIB materials.